Editorial: risk factors for persistent villus atrophy in coeliac disease – is it time to reconsider definitions for refractory coeliac disease? Authors' reply. Issue 11 (5th May 2017) - Mahadev, S.; Murray, J. A.; Green, P. H. R.; Adelman, D. A.; Lebwohl, B.
Abstract : Linked Content This article is linked to Mahadev et al and Braude, Newnham papers. To view these articles visithttps://doi.org/10.1111/apt.13988 andhttps://doi.org/10.1111/apt.14055 .